Modified improvised pre-embedding method for core needle biopsies: A clinicopathologic study - Nikita Sunny; Anupa Thomas; Suraj Manjunath; Usha Kini (Wolters Kluwer Medknow Publications, 2021)
Background: An optimal core needle biopsy (CNB) is expected to balance between tissue diagnosis, the accuracy of negative sampling, and concordance with reports from resected specimens to select the appropriate treatment. Though various techniques for CNBs are available, no guidelines exist for processing CNB, with practices varying from lab to lab for transport and processing. This prospective study aims to design a cost-effective, user-friendly pre-embedding method for CNBs to yield intact cores. Objective: To compare the outcomes of CNBs by a conventional method with those processed by the modified pre-embedded processing protocol over 2 years. Material and Methods: Presurgical CNBs from SOL in various organs were subjected to the conventional free-floating method in formalin (control) for histopathology diagnosis. CNBs from the corresponding, freshly resected SOLs (test) were taken, inked with coloring inks if multiple, placed between two 2 × 2 cm polyurethane foam meshes fitted inside cassettes, fixed in formalin, and transported to the laboratory. The two CNB groups were coded and scored independently for intactness, tissue processing, ease of embedding, and ease of cutting sections. Data obtained were statistically analyzed. Results: Test CNB cores were better processed, intact, linear, and aligned, compared to control CNBs. With four CNBs in one block, the number of blocks and sections were cut-down by one-fourth. Conclusion: CNBs processed using polyurethane foam and coloring inks were superior and economical against conventional free-floating CNBs. This technique can be practiced by surgeons at the bedside.